2016
DOI: 10.4172/2155-9880.1000442
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hypertension and the Eye: Highlighting a Comorbidity

Abstract: Purpose: To identify ocular comorbidity in systemic hypertension. Methods:Research findings include data of 566 patients with RVO ( retinal vein occlusion) 408 and 158 patients with the central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) respectively, representing a cases and and 566 controls, all aged 31 years and older. Excluded from case and control group were persons with degenerative changes of retina and ocular inflammation. At the baseline examination blood pressures was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that 60% of RVO patients were hypertensive patients. 19 According to Hayreh et al, there was a significantly higher prevalence of arterial hypertension in BRVO compared with CRVO and HRVO. 20 However, there are no studies so far showing a pressure trend before the development of RVO.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that 60% of RVO patients were hypertensive patients. 19 According to Hayreh et al, there was a significantly higher prevalence of arterial hypertension in BRVO compared with CRVO and HRVO. 20 However, there are no studies so far showing a pressure trend before the development of RVO.…”
Section: Discussionmentioning
confidence: 98%